Ethical Use of Generative Artificial Intelligence in Islamic Religious Education: Perspectives of Madrasah Aliyah Teachers and Students in Banjarmasin - Muhammad Amin (Al-Munawwarah: Journal of Islamic Education, 2026)
The growing use of generative artificial intelligence (GenAI) in education has created new opportunities for instructional innovation while simultaneously raising concerns regarding academic integrity, cognitive dependence, information accuracy, and ethical responsibility. These concerns are particularly significant in Islamic Religious Education, where learning is directed not only toward knowledge acquisition but also toward the formation of morality, spirituality, and proper conduct. This study examines the ethical use of GenAI from the perspectives of Madrasah Aliyah teachers and students in Banjarmasin. Using a qualitative case study design, data were collected through semi-structured interviews, classroom observations, and document analysis, and were analyzed thematically. The findings show that teachers primarily used GenAI as a pedagogical support tool for preparing materials, contextual examples, discussion questions, and assessments, while students used it to obtain explanations, summarize content, generate ideas, and complete assignments. However, differences emerged in ethical perceptions: teachers emphasized honesty, responsibility, and the learning process, whereas students often prioritized efficiency and convenience. The study also identified risks related to uncritical copying, cognitive dependence, inaccurate religious information, and unclear boundaries of acceptable AI assistance. Responsible use therefore requires the integration of AI literacy with the Islamic principles of ṣidq, amānah, adab, tabayyun, maṣlaḥah, and ḥifẓ al-‘aql. The study concludes that GenAI should function as a wasīlah that supports learning rather than replacing teachers, intellectual effort, or religious authority. Clear institutional guidelines, teacher mediation, source verification, and assessment redesign are necessary to ensure ethical and responsible AI use in madrasah education.